2019
DOI: 10.3390/urbansci3020053
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differences in the Rate of Type 2 Diabetes Among American Cities: How Urbanization Continues to Challenge the Traditional Epidemiological View

Abstract: As the world’s largest urban regions continue to expand, a concomitant rise in non-communicable diseases, particularly type 2 diabetes, poses an increasingly ominous challenge to experts in the field of public health. Given that the majority of the world’s population (54%) resides in urban areas, a figure likely to reach two-thirds by 2050, this issue presents serious implications for medical practitioners as well as policymakers seeking to manage long-term healthcare costs while sustaining historic increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Epidemiological studies have reported the link between urbanization and CVD risk factors such as diabetes and hypertension (Young 2019;Tai et al 2020;Chen et al 2020;Pinchoff et al 2020;Boakye et al 2021;Ostchega et al 2022). Urbanization directly impacts the food environment, choices, and behaviors, with a greater likelihood of adopting Western-style diets and sedentary lifestyles contributing to the prevalence and disparities of cardiometabolic risks.…”
Section: Association Between Levels Of Physical Activity and Chronic ...mentioning
confidence: 99%
“…Epidemiological studies have reported the link between urbanization and CVD risk factors such as diabetes and hypertension (Young 2019;Tai et al 2020;Chen et al 2020;Pinchoff et al 2020;Boakye et al 2021;Ostchega et al 2022). Urbanization directly impacts the food environment, choices, and behaviors, with a greater likelihood of adopting Western-style diets and sedentary lifestyles contributing to the prevalence and disparities of cardiometabolic risks.…”
Section: Association Between Levels Of Physical Activity and Chronic ...mentioning
confidence: 99%